Batman & Robin [videorecording (Blu-Ray)] - Goldenthal, Elliot (Distributed by Warner Home Video, 2010)
The dynamic duo are back and are up against the nefarious Mr. Freeze, who is bent on turning the world into an iceberg. Then, there is the slyly seductive but highly toxic Poison Ivy, who wants to eliminate all animal life and turn the Earth into a gigantic greenhouse. Batman's butler, Alfred, is dying from the same mysterious disease that Freeze's wife has. It's up to Batman, Robin and Alfred's niece, Batgirl, to fight the villains and save Alfred before he dies.